Synthesis of 2-trifluoromethylpyrazolo[5,1-a]isoquinolines via silver triflate-catalyzed or electrophile-mediated one-pot tandem reaction - Zhou, Xiaoli; Liu, Meiling; Luo, Puying; Lai, Yingjun; Yang, Tangtao; Ding, Qiuping (Beilstein Journal of Organic Chemistry, 2014)
An efficient one-pot tandem cyclization/[3 + 2] cycloaddition reaction of N’-(2-alkynylbenzylidene)hydrazides with ethyl 4,4,4-trifluorobut-2-ynoate under silver triflate-catalyzed or electrophile-mediated conditions is described. Various trifluoromethylated pyrazolo[5,1-a]isoquinolines were afforded in moderate to excellent yield by this developed method.
Keywords: [3 + 2] cycloaddition; electrophile; N’-(2-alkynylbenzylidene)hydrazide; silver triflate; tandem